American Indian and Alaska Native Infant and Pediatric Mortality, United States, 1999–2009 - Wong, Charlene A. (American Public Health Association, 2014)
Objectives. We described American Indian/Alaska Native (AI/AN) infant and pediatric death rates and leading causes of death. Methods. We adjusted National Vital Statistics System mortality data for AI/AN racial misclassification by linkage with Indian Health Service (IHS) registration records. We determined average annual death rates and leading causes of death for 1999 to 2009 for AI/AN versus White infants and children. We limited the analysis to IHS Contract Health Service Delivery Area counties. Results. The AI/AN infant death rate was 914 (rate ratio [RR] = 1.61; 95% confidence interval [CI] = 1.55, 1.67). Sudden infant death syndrome, unintentional injuries, and influenza or pneumonia were more common in AI/AN versus White infants. The overall AI/AN pediatric death rates were 69.6 for ages 1 to 4 years (RR = 2.56; 95% CI = 2.38, 2.75), 28.9 for ages 5 to 9 years (RR = 2.12; 95% CI = 1.92, 2.34), 37.3 for ages 10 to 14 years (RR = 2.22; 95% CI = 2.04, 2.40), and 158.4 for ages 15 to 19 years (RR = 2.71; 95% CI = 2.60, 2.82). Unintentional injuries and suicide occurred at higher rates among AI/AN youths versus White youths. Conclusions. Death rates for AI/AN infants and children were higher than for Whites, with regional disparities. Several leading causes of death in the AI/AN pediatric population are potentially preventable.